2011
DOI: 10.1007/s10290-010-0086-2
|View full text |Cite
|
Sign up to set email alerts
|

Does foreign direct investment promote regional development in developed countries? A Markov chain approach for US states

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
0
17
1
Order By: Relevance
“…4. The average per-capita income in the richest U.S. states was about twice as high as in the poorest U.S. states (see also Bode and Nunnenkamp 2011). states (0.18 in 2001). The ten poorest U.S. states hosted just 13% of total inward FDI stocks.…”
Section: Theoretical Background and Previous Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…4. The average per-capita income in the richest U.S. states was about twice as high as in the poorest U.S. states (see also Bode and Nunnenkamp 2011). states (0.18 in 2001). The ten poorest U.S. states hosted just 13% of total inward FDI stocks.…”
Section: Theoretical Background and Previous Findingsmentioning
confidence: 99%
“…One possible reason could be that FDI is not a major source of technological innovation in the United States, as Figini and Görg (1999) suspect. The cross‐country analysis of Figini and Görg (2006, 12) appears to be in line with this reasoning: when splitting their sample into developed and developing host countries, the effect of FDI on inequality turns out to be negative for the former subsample, possibly because “developed countries are already at high levels of technological development.” Similarly, Mullen and Williams (2005) as well as Bode and Nunnenkamp (2011) argue that affiliates of foreign‐based MNEs operating in the technologically most advanced United States may be at the receiving end of technological and knowledge spillovers.…”
Section: Empirical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Bode and Nunnenkamp (2007) investigated the effects of inward FDI on per-capita income and growth of the US states since the mid-1970s. This study analyzed the long-run relationships between inward FDI and economic outcomes in terms of value added and employment at the level of US states (Bode & Nunnenkamp, 2007). The study found that employment-intensive FDI, concentrated in richer states, has been conducive to income growth, while capital-intensive FDI, concentrated in poorer states, has not.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ajaga and Nunnenkamp (2008) find two‐way causality between FDI and economic outcomes. Bode and Nunnenkamp (2011) employ a Markov chain approach to show that (i) both quantitative and qualitative FDI characteristics affect per capita income growth, and (ii) FDI has tended to slow down income convergence among US states. According to Ford, Rork, and Elmslie (2008), US states have to be well endowed with human capital to derive benefits from FDI, similar to Borensztein, DeGregorio, and Lee’s (1998) findings across developing host countries 4 .…”
Section: Introductionmentioning
confidence: 99%